Analysis of Governance and Affirmative Action Policies For The Sale of Native Papuan Products (OAP) in The Central Market of Sorong City - Joice Handayani P Djafar; Rini Werdiningsih; Aris Toening Winarni (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the effectiveness of market governance and the implementation of affirmative policies for Indigenous Papuan traders (OAP) at the Sorong City Central Market in 2026. Using a mixed methods approach with a sequential explanatory design, quantitative data were collected through a survey of 90 OAP trader respondents, followed by in-depth interviews with key informants from government elements and community leaders. The study results show a high level of trader dissatisfaction (58.7%), particularly regarding trade zoning and price protection. Qualitative findings reveal that affirmative policies remain administrative in nature and fail to address spatial marginalization, placing OAP traders in low-accessibility areas. This study recommends restructuring market zoning to be more equitable, standardizing local commodity prices, and digitizing trader data to ensure that Special Autonomy policies are on target. By addressing these core issues, it is hoped that the market environment in Sorong City will be more inclusive and supportive of OAP traders, fostering economic empowerment in line with the goals of Special Autonomy.